Prospective Evaluation of the Concordance of Commercial Circulating Tumor DNA Alterations with Tumor-Based Sequencing across Multiple Soft Tissue Sarcoma Subtypes - Bryce Demoret (Cancers, 2019)
Soft tissue sarcomas (STS) are diverse tumors with heterogenous alterations. Platforms to detect circulating tumor DNA (ctDNA) have rapidly increased in popularity as they may avoid invasive biopsy morbidity. However, ctDNA profiling concordance with standard solid tumor comprehensive genomic profiling (CGP) is poorly characterized. Here, we report the outcomes of a single-institution experience comparing mutational results from commercial ctDNA and solid tumor CGP in advanced STS subjects. We identified STS subjects who had undergone solid tumor based CGP in four distinct cohorts: Dedifferentiated liposarcoma (DDLPS), leiomyosarcoma (LMS), undifferentiated pleomorphic sarcoma (UPS), and gastrointestinal stromal tumor (GIST). Subjects with radiographically measurable tumor were profiled using a commercial ctDNA CGP panel. Overlapping genes/exons on both biopsy panels were analyzed. Twenty-four subjects completed both ctDNA and solid tumor CGP. ctDNA was detected in 18/24 subjects. Subject level concordance rates in all overlapping genes were: LMS = 4/6; UPS = 2/6; DDLPS = 1/6; GIST = 0/6. Copy number alterations were notably poorly concordant. For subjects with short variant alterations and detectable tumor fractions, concordance with solid tumor CGP was 76% (13/17). LMS subjects had the highest median tumor fraction and concordance. No correlation was seen between tumor fraction or radiographic tumor volume largely driven by low estimated tumor fraction. A limitation of the study is that only targeted sequencing was performed. However, given the poor concordance in commonly altered genes, ctDNA panels in sarcoma cannot be broadly applied. Further, more extensive studies will need to be performed.